Car Hacks and Mods for Dummies - Vespremi, David (Wiley Publishing, 2011)
So you want to turn your Yugo into a Viper? Sorry--you need a certified magician. But if you want to turn your sedate sedan into a mean machine or your used car lot deal into a powerful, purring set of wheels, you’ve come to the right place. Car Hacks & Mods for Dummies will get you turbo-charged up about modifying your car and guide you smoothly through: